An Analysis of Accountability, Compliance, and Regional Financial Management Performance - Dito Aditia Darma Nst; Rinawati Tumanggor; Minar Berutu; Jeff Sibuea; Antonius Piaman Telaumbanua (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Regional financial management in the era of decentralization demands absolute transparency and accountability from local governments to the public. This article is the result of a Public Sector Audit Project aimed at critically analyzing the interrelationship among the three main pillars of auditing: financial accountability, regulatory compliance, and performance effectiveness through the Value for Money framework (3E: Economy, Efficiency, and Effectiveness). The methodology employed is descriptive qualitative research using document analysis techniques on Audit Reports (Laporan Hasil Pemeriksaan/LHP) and regional financial management regulations. The findings reveal an “accountability paradox,” where the achievement of an Unqualified Opinion (Wajar Tanpa Pengecualian/WTP) does not fully correlate with the absence of corruption practices or improvements in public welfare. The study identifies procurement of goods and services as well as grant expenditures as areas particularly vulnerable to non-compliance. Furthermore, the effectiveness aspect of budgeting is often neglected due to the predominantly administrative focus of audits. This article recommends transforming the role of Government Internal Supervisory Apparatus (APIP) into strategic partners, strengthening auditor independence, and integrating information technology–based audits to mitigate maladministration risks and ensure tangible economic benefits for society.